Analysis of the Sociological Approach of Short Story Literature "Robohnya Surau Kami" by A.A. Navis - Caecilia Fani Sulistyaningrum*; Setya Tri Nugraha (Riwayat: Educational Journal of History and Humanities, 2024)
This research analyzes the short story "Robohnya Surau Kami" by A.A. Navis from the sociological approach to literature, focuses on the value of social, cultural, and religious aspects. This short story describes the condition of the Minangkabau people who are facing social and cultural changes, especially related to social concerns, traditional cultural values, and religious practices. Through its characters, this short story criticizes the indifference, lack of social responsibility, and indifference to religious values which have resulted in the collapse of spiritual values in society. Literary sociology methods help in understanding the relationship between literary works and their socio-cultural context, as well as revealing the moral messages and social criticism contained in the stories. From a social aspect, this short story highlights social solidarity, lack of social responsibility, and criticism of society's indifference. Cultural aspects are presented through communal life, traditions, and respect for community figures. Meanwhile, from a religious aspect, this short story shows obedience in worship, the important role of religious institutions, persistence in studying religion, and the existence of religious figures as spiritual leaders. Thus, this short story is not only a narrative, but also a reflection and criticism of social reality, inviting readers to reflect on the values and changes in their society.